The effect of blanching and storage on the chemical composition of dates - Hamood H. Mutlak (1980)
The changes during storage of dates. (Phoenix dactylifera L.) at room temperature and at -13° were studied. The effect of blanching in boiling water and by microwave heating before storage was also studied. Moisture, pH, acidity, total soluble solids, sugar, colour, soluble leucoanthocyanidin tannin, insoluble leucoanthocyanidin tannin, total soluble phenolic compounds and the activities of polyphenolase and peroxidase enzymes were investigated. The dates stored at room temperature showed darkening, and decrease in the amount of insoluble leucoanthocyanidin tannin. The dates stored at -13° showed darkening, decrease in the total soluble phenolic compounds, increase in the insoluble leucoanthacyanidin tannin and increase in the total soluble solids. [Continues.]